2016
DOI: 10.1002/14651858.cd006417.pub3
|View full text |Cite
|
Sign up to set email alerts
|

School-based interventions for preventing HIV, sexually transmitted infections, and pregnancy in adolescents

Abstract: BackgroundSchool-based sexual and reproductive health programmes are widely accepted as an approach to reducing high-risk sexual behaviour among adolescents. Many studies and systematic reviews have concentrated on measuring effects on knowledge or self-reported behaviour rather than biological outcomes, such as pregnancy or prevalence of sexually transmitted infections (STIs).ObjectivesTo evaluate the effects of school-based sexual and reproductive health programmes on sexually transmitted infections (such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
157
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 124 publications
4
157
0
10
Order By: Relevance
“…Several kinds of evidence are available on the causal link between education and fertility timing, including both experimental randomized controlled trials (Mason‐Jones et al. ) and observation‐based studies. Using longitudinal data, a number of studies have shown that the link between education and later childbearing remains when controlling for family environment and parental characteristics (Marini , ; Rindfuss et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinds of evidence are available on the causal link between education and fertility timing, including both experimental randomized controlled trials (Mason‐Jones et al. ) and observation‐based studies. Using longitudinal data, a number of studies have shown that the link between education and later childbearing remains when controlling for family environment and parental characteristics (Marini , ; Rindfuss et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review of randomized controlled trials of school‐based interventions related to sex education found that intervention to retain young people in secondary school reduced adolescent pregnancy, providing strong evidence for a causal relationship (Mason‐Jones et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…La adolescencia ha sido reconocida como etapa prioritaria en los ODS, especialmente en los ámbitos de salud sexual y reproductiva, y el en acceso apropiado a servicios de salud en tanto derechos humanos (28). Los hallazgos presentados van en esta línea, principalmente en lo que respecta a dar relevancia a la participación de adolescentes en salud tomando en consideración sus necesidades explícitas en SSR.…”
Section: Discussionunclassified
“…En dicho modelo se coordinan las acciones de salud y educación en el espacio educativo, y los equipos de salud realizan actividades y atención permanente a niños y adolescentes desde temprana edad como parte del currículo escolar. La escuela, como territorio cotidiano donde habita la población infantojuvenil, se constituye así en espacio privilegiado para promover conductas protectoras en materia de sexualidad, lo cual ha sido comprobado en diversos contextos del mundo (28,30). En esta iniciativa en particular, los diversos actores entrevistados consideran que se satisfacen las necesidades adolescentes en materia de SSR en mayor medida que en los modelos donde salud y educación operan en forma independiente.…”
Section: Discussionunclassified
“…Although significant progress has been made since the introduction of the teenage pregnancy strategy in 2001, within the UK there is very limited evidence that school-based SRE itself has any kind of significant behavioural or attitudinal impact on young people (Mason-Jones et al, 2016). Daniel Wight says "The evaluations of three different sex education programmes in Britain suggest that improved sex education of a kind that can be readily sustained in British schools, whether teacherdelivered, peer-delivered, or multi-component, is unlikely to have a greater impact on sexual behaviour than that already achieved by current health promotion initiatives.…”
Section: Introductionmentioning
confidence: 99%